2022
DOI: 10.1097/ta.0000000000003528
|View full text |Cite
|
Sign up to set email alerts
|

Preperitoneal packing versus angioembolization for the initial management of hemodynamically unstable pelvic fracture: A systematic review and meta-analysis

Abstract: This SRMA compares the use of angioembolization versus pre-peritoneal packing for the management of bleeding pelvic ring injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…This can be attributed to the proficient surgical skills and extensive clinical experience of the surgical team coupled with the significant advancements in interventional techniques and the enhancement of embolization materials in recent years. Consistent with this, a review by McDonogh et al 8 of literature published from 2000 to 2020 indicated a gradual, albeit subtle, decline in the overall mortality rate among patients who underwent AE, a trend not observed in the EPP group.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This can be attributed to the proficient surgical skills and extensive clinical experience of the surgical team coupled with the significant advancements in interventional techniques and the enhancement of embolization materials in recent years. Consistent with this, a review by McDonogh et al 8 of literature published from 2000 to 2020 indicated a gradual, albeit subtle, decline in the overall mortality rate among patients who underwent AE, a trend not observed in the EPP group.…”
Section: Discussionmentioning
confidence: 65%
“…21 With the ongoing advancements in medical instruments, materials, and AE techniques, increasing numbers of trauma centers are adopting AE as the preferred treatment method. 8 Conversely, EPP is a more invasive procedure that requires a follow-up surgery to remove the pelvic packing, thereby significantly elevating the risk of infection. 13,14 Consequently, our center predominantly performs AE, which explains the disparity in the sample sizes between the two groups in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempting to directly compare outcomes of the various therapeutic interventions for bleeding control from pelvic fractures, is very difficult and may lead to the wrong conclusions, because of the bias and major heterogeneity of the reported study populations. In addition, the major changes in the resuscitation and blood transfusion protocols in the last few years make any outcome comparisons between older and more recent studies unreliable [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors expressed concern that PPP may potentially delay the definitive treatment of angiographic intervention, which was highly effective in this series. McDonogh et al, in a systematic review and meta-analysis of 18 studies with a total of 579 patients, of which 402 were treated with PPP and 177 with angioembolization, reported that 27% of patients treated with PPP did not achieve bleeding control and required subsequent angioembolization [12].…”
Section: Discussionmentioning
confidence: 99%